Performance analysis of a horn-type rudder implementing the Coanda effect - Dae-Won Seo; Jungkeun Oh; Jinho Jang (International Journal of Naval Architecture and Ocean Engineering, 2017)
The Coanda effect is the phenomenon of a fluid jet to stay attached to a curved surface; when a jet stream is applied tangentially to a convex surface, lift force is generated by increase in the circulation. The Coanda effect has great potential to be applied practically applied to marine hydrodynamics where various lifting surfaces are being widely used to control the behavior of ships and offshore structures. In the present study, Numerical simulations and corresponding experiments were performed to ascertain the applicability of the Coanda effect to a horn-type rudder. It was found that the Coanda jet increases the lift coefficient of the rudder by as much as 52% at a jet momentum coefficient of 0.1 and rudder angle of 10°.